Organic-inorganic hybrid light conversion agent, preparation method thereof and light conversion adhesive film

By designing an organic-inorganic hybrid transpressant, using a combination of benzene and triazol, triazine, and photoresital metal oxides to solve the problem of aging yellow changes in EVA glue film, and achieve efficient ultraviolet light Absorbing and stable photoelectric conversion efficiency.

CN119330938AActive Publication Date: 2025-01-21SUZHOU YISHENG OPTICAL MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411877634.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Among the existing photovoltaic packaging materials, EVA films are prone to aging and yellowing after long use outdoors, resulting in a decrease or failure of the photoelectric conversion efficiency of solar cells. The existing light converter cannot be compatible with the substrate and stable. sex.

Method used

A organic-inorganic hybrid turning agent is prepared through the molecular design. The transpressant consists of phenyl and triazol, triazine, and photosensitive metal oxide crystal. Wide -spectrum ultraviolet absorption and high stability transit.

Benefits of technology

The organic-inorganic hybrid light-converting agent has wide UV absorption in the range of 250-400nm, improves the photoelectric conversion efficiency of solar cells, avoids damage to the substrate adhesive film by UV light, and has both high stability and Good compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330938A_ABST
    Figure CN119330938A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of photovoltaic materials. The invention relates to an organic-inorganic hybrid light conversion agent, a preparation method thereof and a light conversion adhesive film, and the preparation method of the organic-inorganic hybrid light conversion agent comprises the following steps: carrying out substitution reaction on benzotriazole and liquid bromine to obtain an intermediate product I; carrying out substitution reaction on the intermediate product I and bromo-ester to obtain an intermediate product II; carrying out coupling reaction on the intermediate product II and 4-(aniline) phenylboronic acid to obtain an intermediate product III; the intermediate product III and 2, 4, 6-trichloro-1, 3, 5-triazine are subjected to a substitution reaction, and an intermediate product IV is obtained; carrying out substitution reaction on the intermediate product IV and an aminobenzoic acid derivative to obtain an intermediate product V; the intermediate product V and photosensitive metal oxide whiskers are subjected to surface modification, and the organic-inorganic hybrid light conversion agent is obtained. According to the invention, the problems of narrow and single absorption peak, low light utilization rate, poor stability, easy precipitation and the like of the conventional organic light conversion agent benzotriazole for packaging adhesive films are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an organic-inorganic hybrid light conversion agent and a preparation method thereof and a light conversion adhesive film. The invention belongs to the field of photovoltaic materials. Background Art

[0002] EVA (ethylene-vinyl acetate copolymer) is a thermoplastic polymer material. As a solar cell packaging material, it has many advantages, including low cost, easy molding, outstanding optical properties, excellent mechanical properties and electrical properties. However, if used for a long time in harsh outdoor climate environments, EVA will age and yellow, resulting in a decrease in the photoelectric conversion efficiency of the battery components or failure due to short circuit damage. Ultraviolet aging is precisely the main factor causing the yellowing of EVA film. The current technology is to add ultraviolet absorbers to EVA to reduce the damage of ultraviolet rays to EVA film. The addition of ultraviolet absorbers converts ultraviolet light into low-energy heat energy, which cannot be used by solar cells, resulting in the loss of light energy and reducing the efficiency of solar cells.

[0003] Therefore, it is necessary to develop a packaging material that can completely absorb the ultraviolet light in the sun and convert it into visible light that can be used by battery components, namely, a light-converting film. This can not only effectively prevent ultraviolet light from damaging battery components, but also increase the photoelectric conversion efficiency of the battery.

[0004] The key to developing encapsulated light-converting adhesive films is to develop efficient and stable light-converting agents. According to literature, inorganic light-converting agents have advantages in stability, but there are compatibility issues with the matrix, which affects the light-conversion efficiency; while organic light-converting agents have more advantages in price, structure, and compatibility with the film; but there is a problem of poor stability. Despite the above problems, most of the current research is still focused on organic light-converting agents. One of the typical ones is the organic light-converting agent based on benzotriazole, which has only one absorption peak, about 350nm, and a narrow effective absorption range. The absorption of ultraviolet light below 400nm is not sufficient. This will cause the corresponding light-converting adhesive film to be unable to effectively absorb ultraviolet rays in sunlight, and thus cannot effectively protect the battery components; the problem of poor stability has not yet been solved.

[0005] In view of the advantages and disadvantages of organic and inorganic light conversion agents, it is necessary to design a new type of light conversion agent that has both the compatibility of organic light conversion agents and the stability of inorganic light conversion agents to solve the technical problems existing in the existing industry. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an organic-inorganic hybrid light conversion agent for photovoltaics, in view of the problem that the light conversion agent used in the encapsulated light conversion adhesive film in the prior art cannot have both compatibility with the substrate and stability. The present invention prepares an organic-inorganic hybrid light conversion agent by molecular design, and effectively solves the above problems through formula design, and has broad application potential. The technical solution adopted by the present invention to solve its technical problems is: A method for preparing an organic-inorganic hybrid light conversion agent comprises the following steps: S11, subjecting benzotriazole to a substitution reaction with liquid bromine to obtain an intermediate product I; S12, subjecting the intermediate product I to a substitution reaction with a bromoester to obtain an intermediate product II; S13, coupling the intermediate product II with 4-(aniline)phenylboronic acid to obtain an intermediate product III; S14, subjecting the intermediate product III to a substitution reaction with 2,4,6-trichloro-1,3,5-triazine to obtain an intermediate product IV; S15, subjecting the intermediate product IV to a substitution reaction with an aminobenzoic acid derivative to obtain an intermediate product V; S16, surface modification of the intermediate product V and photosensitive metal oxide whiskers to obtain an organic-inorganic hybrid light conversion agent.

[0007] Furthermore, the molar ratio of the benzotriazole to the liquid bromine is 1:(1.2-1.5).

[0008] Furthermore, the molar ratio of the intermediate product I to the bromoester is 1:(1.2-1.5).

[0009] Furthermore, the molar ratio of the intermediate product II to the 4-(aniline)phenylboronic acid is 1:(1.2-1.6).

[0010] Furthermore, the molar ratio of the intermediate product III to the 2,4,6-trichloro-1,3,5-triazine is (2.0-2.2):1.

[0011] Furthermore, the molar ratio of the intermediate product IV to the aminobenzoic acid derivative is 1:(1.0-1.2); the aminobenzoic acid derivative has 1 amino functional group and 1-3 carboxyl functional groups.

[0012] Furthermore, the mass ratio of the intermediate product V to the photosensitive metal oxide whisker is (0.5-2.0):10; the photosensitive metal oxide whisker is selected from at least one of zinc oxide, titanium oxide and copper oxide.

[0013] Another object of the present invention is to provide an organic-inorganic hybrid light conversion agent prepared by the preparation method described above.

[0014] Another object of the present invention is to provide a light conversion adhesive film, comprising the organic-inorganic hybrid light conversion agent as described above.

[0015] Further, the following raw materials are included in parts by weight: 100 parts of polyolefin resin; Cross-linking agent 0.5-1.5 parts; 1.0-3.0 parts of auxiliary cross-linking agent; 2.0-10.0 parts of the organic-inorganic hybrid light conversion agent; Antioxidant 0.05-0.25 parts; Light stabilizer 0.05-0.3 parts; Coupling agent 0.3-0.8 parts.

[0016] Furthermore, the polyolefin resin is selected from at least one of EVA resin and POE resin.

[0017] Beneficial effects of the present invention: (1) The present invention provides an organic-inorganic hybrid light conversion agent for photovoltaics, which is a structure in which triazine-modified benzotriazole (organic structure) modifies the surface of a photosensitive metal oxide (inorganic structure), wherein the modified benzotriazole structure contains a large number of chemical structures such as benzene rings, triazine rings, and long fatty chain ester structures; first, the molecular structure of benzotriazole is designed, and phenyl substitution can change its symmetry, so that it has a wide ultraviolet absorption at 300-400nm, and triazine has a large absorption at 200-330nm in the ultraviolet region, so the triazine-modified benzotriazole structure can have a wide absorption in the range of 250-400nm; second, benzotriazole, triazine, and photosensitive metal oxide in the organic-inorganic hybrid light conversion agent excite carriers after absorbing ultraviolet light, and transfer energy through the conjugated structure and the photogenerated hole recombination effect of the photosensitive metal oxide; at the same time, the whisker structure of the photosensitive metal oxide has a larger specific surface area, which can have The organic light-conversion structures are effectively connected in series to form a large conductive structural unit, thereby greatly improving the light-conversion efficiency; third, the benzotriazole and triazine structures are both rigid structures, which can reduce the energy loss caused by the vibration of the molecular structure during the molecular luminescence process, and further improve the light-conversion efficiency; fourth, the photosensitive metal oxide whisker structure has a special spatial structure, and the needle-like structure of the whisker can effectively increase the contact probability between the conductive structural units, forming a conductive network, and further improving the light-conversion efficiency; fifth, the whisker structure in the photosensitive metal oxide whisker structure gives the light-conversion agent a better anchoring effect and has low mobility; sixth, after the triazine-modified benzotriazole modifies the photosensitive metal oxide, it gives the light-conversion agent better system compatibility, and the long fatty chain ester structure in the organic structure is conducive to its dispersibility in the polyolefin matrix, synergistically improving the physical properties, etc.; finally, the organic-inorganic hybrid light-conversion agent has the advantages of both the good stability of the inorganic light-conversion agent and the good dispersibility of the organic light-conversion agent.

[0018] (2) The present invention provides a light-converting adhesive film. The organic-inorganic hybrid light-converting agent in the formula system converts the ultraviolet light that is originally absorbed by the ultraviolet light absorber and lost into visible light, making full use of the light, improving the photoelectric conversion efficiency of the solar cell, and avoiding the damage of the ultraviolet light to the base film, which has great practical significance.

[0019] (3) The present invention provides a method for preparing an organic-inorganic hybrid light conversion agent. The light conversion agent in the formula system is prepared using common raw materials, and the light conversion film is designed through the formula and also has the effect of an auxiliary light stabilizer, which is conducive to the industrialization of the product of the present invention and has strong operability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0021] FIG1 is a hydrogen NMR spectrum of the intermediate product I in Example 1 of the present invention; FIG2 is a hydrogen NMR spectrum of intermediate product II in Example 1 of the present invention; FIG3 is a hydrogen NMR spectrum of the intermediate product III in Example 1 of the present invention; FIG4 is a hydrogen NMR spectrum of the intermediate product IV in Example 1 of the present invention; FIG5 is a hydrogen NMR spectrum of the intermediate product V in Example 1 of the present invention; FIG6 is a hydrogen NMR spectrum of the organic-inorganic hybrid light conversion agent in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0023] The purpose of the present invention is to develop an organic-inorganic hybrid light conversion agent and light conversion adhesive film for photovoltaics to meet the application requirements of existing photovoltaic packaging materials. The idea of ​​realization is: to prepare a self-made organic-inorganic hybrid light conversion agent for photovoltaics, while ensuring its compatibility and dispersibility in polyolefins, and having high stability and light conversion efficiency. Specifically: using benzotriazole as a parent body for asymmetric modification, electron-rich structure benzene ring, and triazine bonding modification; and surface modification of photosensitive metal oxide whiskers to form an organic-inorganic hybrid structure. The theoretical basis of realization is: benzotriazole first undergoes a substitution reaction with liquid bromine, then a substitution reaction with bromoester, followed by a coupling reaction with phenylboronic acid, then a substitution reaction with secondary amino group, and then a substitution reaction with amino group, and finally a surface modification reaction of carboxyl group with metal oxide to prepare an organic-inorganic hybrid light conversion agent. The above-mentioned organic-inorganic hybrid light conversion agent has a larger absorption peak, higher compatibility and stability with the matrix, and higher light conversion efficiency, etc. through molecular structure design, and does not migrate and precipitate. The implementation method of the present invention is as follows: The present invention provides a method for preparing an organic-inorganic hybrid light conversion agent, comprising the following steps: S11, add benzotriazole to hydrobromic acid, stir, slowly drop liquid bromine into the reaction system, heat and reflux for 18-24 hours, add saturated sodium bisulfite aqueous solution to quench, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and dry under vacuum at 40°C for 8 hours to obtain intermediate I; The usage ratio of benzotriazole, hydrobromic acid, liquid bromine, saturated sodium bisulfite aqueous solution, dichloromethane and anhydrous sodium sulfate is 0.1 mol: 0.75 mol: 0.12-0.15 mol: 400 mL: 300 mL: 5 g.

[0024] S12, take the intermediate product I, potassium carbonate and bromoester, add them to N,N-dimethylformamide, stir and heat at 40-60°C for 40-48h, cool to room temperature after the reaction is completed, wash with saturated ammonium chloride solution three times, extract with ethyl acetate, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 5, V / V), and dry in vacuo at 40°C for 8h to obtain the intermediate product II.

[0025] The usage ratio of intermediate product I, potassium carbonate, bromoester, N,N-dimethylformamide, saturated ammonium chloride solution, ethyl acetate and anhydrous sodium sulfate is 0.1 mol: 0.25 mol: 0.12-0.15 mol: 200 mL: 300 mL: 400 mL: 5 g.

[0026] The carbon number of the bromoester is C6-C 10 , so as to avoid the number of C atoms being greater than 10, the reaction activity being low, affecting the reaction efficiency and having an adverse effect on the subsequent reaction efficiency products; the number of C atoms being less than 6, the molecular chain being too small to form a good compatibility with the matrix resin, affecting the product performance; therefore, the bromoester in the present invention can be ethyl 4-bromovalerate, ethyl 5-bromovalerate, ethyl 6-bromohexanoate, ethyl 7-bromoheptanoate, tert-butyl 5-bromovalerate, ethyl 8-bromooctanoate, etc.; and tert-butyl 5-bromovalerate is preferred.

[0027] S13, take the intermediate product II, 4-(aniline)phenylboronic acid, potassium carbonate, and tetrakis(triphenylphosphine)palladium, mix them and add them to the reactor, and perform N2 replacement protection; after adding the mixed solvent, stir and heat under reflux for 12-24 hours, add deionized water for oscillation, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and dry under vacuum at 40°C for 8 hours to obtain the intermediate product III.

[0028] The usage ratio of intermediate product II, 4-(aniline)phenylboronic acid, potassium carbonate, tetrakis(triphenylphosphine)palladium, mixed solvent, deionized water, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.12-0.16 mol: 0.5 mol: 0.005-0.01 mol: 150 mL: 200 mL: 300 mL: 5 g; The mixed solvent is toluene, n-butanol, and deionized water in a volume ratio of 3:5:1.

[0029] In the coupling reaction of 4-(aniline)phenylboronic acid and intermediate product II of the present invention, a boronic acid group and a secondary amino group may exist simultaneously to undergo substitution coupling reaction with bromine in intermediate product II, respectively. However, the reactivity of the boronic acid group is higher than that of the secondary amino group, and the coupling reaction of the secondary amino group usually requires the presence of a strong base. Therefore, under the same conditions, the boronic acid group preferentially undergoes coupling reaction with the bromobenzene structure.

[0030] S14, the reaction system is replaced with N2 gas and protected with nitrogen, the intermediate product III is added to tetrahydrofuran A, magnetically stirred, n-butyl lithium is added, ice bath is placed, stirred for 15 minutes, and then added dropwise to tetrahydrofuran B containing 2,4,6-trichloro-1,3,5-triazine using a peristaltic pump. After the addition is completed, the mixture is heated under reflux for 5-8 hours; cooled to room temperature, deionized water is injected, stirred for 15 minutes, insoluble matter is obtained, the insoluble matter is filtered out, recrystallized with dichloromethane and n-hexane, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0031] The dosage ratio of the intermediate product III, tetrahydrofuran A, n-butyl lithium, 2,4,6-trichloro-1,3,5-triazine, tetrahydrofuran B, and deionized water is 0.20-0.22 mol: 200 mL: 0.20-0.25 mol: 0.1 mol: 300 mL: 800 mL.

[0032] S15, take the intermediate product IV and the aminobenzoic acid derivative, add them to anhydrous tetrahydrofuran, heat and reflux for 10-20 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, add saturated saline solution, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0033] The dosage ratio of the intermediate product IV, aminobenzoic acid derivative, anhydrous tetrahydrofuran, saturated saline solution and deionized water is 0.1 mol: 0.10-0.12 mol: 200 mL: 300 mL: 500 mL.

[0034] The aminobenzoic acid derivative has 1 amino functional group and 1-3 carboxyl functional groups; The aminobenzoic acid derivative having 1 carboxyl functional group may be p-aminobenzoic acid, m-aminobenzoic acid, 4-amino-3-methylbenzoic acid, 4-amino-2-methylbenzoic acid, 3-amino-4-methylbenzoic acid, 2-amino-4-methylbenzoic acid, etc.; and p-aminobenzoic acid is preferred; The aminobenzoic acid derivative having 2 carboxyl functional groups may be 4-aminophthalic acid, 4-aminoisophthalic acid, etc.; and 4-aminophthalic acid is preferred; The aminobenzoic acid derivative having 3 carboxyl functional groups may be 2-aminobenzene-1,3,5-tricarboxylic acid, 1-aminobenzene-3,4,5-tricarboxylic acid, etc., and preferably 1-aminobenzene-3,4,5-tricarboxylic acid.

[0035] S16, adding the intermediate product V and the photosensitive metal oxide whiskers into anhydrous acetone, stirring magnetically at 80-90° C. for 2-3 hours, introducing the mixture into a watch glass, and vacuum drying at 100° C. for 48 hours to obtain the intermediate product V, i.e., the organic-inorganic hybrid light conversion agent.

[0036] The usage ratio of the intermediate product V, the photosensitive metal oxide whisker and the anhydrous acetone is 0.5-2.0 g: 10 g: 200 mL.

[0037] The photosensitive metal oxide whiskers are zinc oxide, titanium oxide or copper oxide; The preferred zinc oxide whisker of the present invention is a four-needle zinc oxide whisker with a special three-dimensional structure; it is purchased from Chengdu Jiaoda Jingyu Technology Co., Ltd., with a brand name of AT-01 and a specification of 10-20 μm.

[0038] The preferred method for preparing titanium oxide whiskers is prepared according to the method described in the literature (Zhang Yanping et al.; Preparation and Oil Solubility of TiO2 Nanowhiskers [J]. Journal of Bohai University (Natural Science Edition), 2017, 38(2): 156-160)), which is a nanowire structure with a diameter of 60-100nm and an aspect ratio of 25:1.

[0039] The preparation method of copper oxide whiskers is based on the method described in the literature (Li Su et al.; Preparation of copper oxide whiskers by electrochemical method [J]: 2010, 61: 112-115.), and is a one-dimensional structure with a diameter of 60-100 nm, a length of 0.5-1 μm, and an aspect ratio of 8-10.

[0040] The photosensitive metal oxide whisker structure in the present invention can be specifically zinc oxide whisker, titanium oxide whisker, and copper oxide whisker. First, the light conversion efficiency of zinc oxide, titanium oxide, and copper oxide as light conversion agent structures can reach a relatively high level; second, in terms of physical structure, the zinc oxide whisker can be a four-needle zinc oxide whisker, which is a three-dimensional four-needle shape with a regular three-dimensional spatial structure; four needle-shaped crystals extend from the core radial direction, each needle-shaped body is a single crystal microfiber, and the needle-shaped body is nanometer-level; it can effectively increase the contact probability of each needle-shaped body and form a conductive path to the greatest extent; at the same time, the four-needle spatial structure can make it effectively and evenly dispersed in the matrix, and the overall performance such as anchoring effect is better; titanium oxide whiskers and copper oxide whiskers are one-dimensional nanowire structures, which have good light conversion and conductivity properties and low mobility and other properties.

[0041] The preparation process of the organic-inorganic hybrid light conversion agent in the present invention is as follows, which is only for reference and does not constitute a limitation of the present invention: .

[0042] Another object of the present invention is to provide an organic-inorganic hybrid light conversion agent, which is prepared by the method as described above.

[0043] The organic-inorganic hybrid light conversion agent in the present invention is an organic structure modified with an inorganic structure, specifically a triazine-modified benzotriazole modified photosensitive metal oxide whisker. The inorganic structure is modified by the organic structure to effectively improve the dispersibility of the inorganic structure in the matrix; and through molecular structure design, triazine, asymmetric benzotriazole, and long-chain ester groups are used to improve the compatibility with the matrix. The triazine, benzene ring, benzotriazole, etc. in the light conversion agent form a conjugated structure, which effectively broadens the absorption peak width in the ultraviolet region, improves the electron transmission capacity, and improves the light conversion efficiency; at the same time, the whisker structure anchors the matrix, increases the contact probability of each light conversion structural unit, and forms a conductive network of a "quasi-macromolecule" structure on a macro scale, which can effectively improve the luminous efficiency, photoelectric gain and other performances. In the structure of the organic-inorganic hybrid light conversion agent in the present invention, each chemical structure has a synergistic effect of promoting the improvement of light conversion efficiency.

[0044] The present invention also provides a light-converting adhesive film, the raw materials of which include the organic-inorganic hybrid light-converting agent as described above; specifically, the raw materials preferably include the following parts by weight: 100 parts of polyolefin resin; Cross-linking agent 0.5-1.5 parts; 1.0-3.0 parts of auxiliary cross-linking agent; 2.0-10.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.05-0.25 parts; Light stabilizer 0.05-0.3 parts; Coupling agent 0.3-0.8 parts.

[0045] Furthermore, the polyolefin resin is selected from at least one of EVA resin and POE resin.

[0046] Wherein, when the polyolefin resin is EVA resin, the light-converting adhesive film preferably comprises the following raw materials in parts by weight: EVA resin 100 parts; Cross-linking agent 0.5-1.5 parts; 1.0-3.0 parts of auxiliary cross-linking agent; 2.0-10.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.1-0.25 parts; Light stabilizer 0.1-0.3 parts; Coupling agent 0.3-0.5 parts.

[0047] When the polyolefin resin is POE resin, the light-converting adhesive film preferably includes the following raw materials in parts by weight: POE resin 100 parts; Cross-linking agent 0.5-1.5 parts; 1.0-3.0 parts of auxiliary cross-linking agent; 2.0-10.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.05-0.20 parts; Light stabilizer 0.05-0.20 parts; Coupling agent 0.4-0.8 parts.

[0048] The EVA resin in the present invention preferably has a VA content of 28-33%. Unless otherwise specified, the preferred EVA resin in the following embodiments and comparative examples of the present invention is purchased from DuPont, USA, with a VA content of 33% and a melt index (MI) of 31.

[0049] Unless otherwise specified, the POE resin in the following examples and comparative examples of the present invention has a model number of XUS38660 and is purchased from The Dow Chemical Company of the United States.

[0050] The crosslinking agent in the present invention is an organic peroxide, specifically benzoyl peroxide, 2,5-dimethyl-2,5-bis(benzoylperoxide)hexane, dicyclohexyl peroxycarbonate or diisopropylbenzene peroxide, etc.; unless otherwise specified, the crosslinking agent in the following embodiments and comparative examples of the present invention is benzoyl peroxide.

[0051] The auxiliary cross-linking agent in the present invention is a multifunctional allyl group and / or acryloxy group.

[0052] The allyl cross-linking aid may be triallyl cyanurate or triallyl isocyanurate.

[0053] The acryloxy-based auxiliary cross-linking agent may be any combination of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and pentaerythritol triacrylate.

[0054] Unless otherwise specified, the auxiliary crosslinking agents in the following examples and comparative examples of the present invention are triallyl isocyanurate, trimethylolpropane trimethacrylate, and propoxylated trimethylolpropane triacrylate, which are added in a mass ratio of 10:2:4.

[0055] The antioxidant in the present invention is a combination of hindered phenols and phosphites. The hindered phenol antioxidant may be antioxidant 1010, antioxidant 1076, antioxidant 264, antioxidant 2246, etc.; and antioxidant 1010 is preferred. The phosphite antioxidant may be antioxidant 168, antioxidant 242, antioxidant TPP, etc.; and antioxidant 168 is preferred. Unless otherwise specified, the antioxidant in the following examples and comparative examples of the present invention is antioxidant 1010 and antioxidant 168 added in a mass ratio of 1:2.

[0056] In the present invention, the light stabilizer is a hindered amine light stabilizer to avoid competition with the light conversion agent for ultraviolet rays. The hindered amine light stabilizer can be UV-292, UV-770 or GW540, etc., and UV-292 is preferred. Unless otherwise specified, the light stabilizer in the following examples and comparative examples of the present invention is UV-292.

[0057] In the following embodiments of the present invention, the coupling agent is a silane coupling agent, specifically a vinyl silane coupling agent, which may be KH151, KH171 or KH172, etc., and KH172 is preferred.

[0058] In order to better understand the above invention, the present invention also provides a method for preparing a light-converting adhesive film. Unless otherwise specified, the method is performed as follows, including the following steps: S21, mixing, i.e. Add the raw materials according to the formula ratio into a mixer, mix and stir at a temperature of 40° C. and a rotation speed of 80 rpm for 2 h to obtain a mixed raw material; S22, extrusion; Specifically, the EVA extrusion process is as follows: The mixed raw materials in S21 are placed in a twin-screw extruder, melt-blended and extruded at a temperature of 80°C in the first zone, 90°C in the second zone, 98°C in the third zone, a die temperature of 102°C, and a rotation speed of 50 rpm, and the mixture is cast through a cast film die and cooled through a casting roller; The POE extrusion process is as follows: The mixed raw materials in S21 are placed in a twin-screw extruder, melt blended and extruded at a temperature of 90°C in the first zone, 100°C in the second zone, 105°C in the third zone, a die temperature of 110°C, and a rotation speed of 50 rpm, and the mixture is cast through a cast film die and cooled through a casting roller; The EPE co-extrusion process is as follows: The EVA layer raw material in S21 is placed in a twin-screw extruder, and melt blended at a temperature of 80°C in the first zone, 90°C in the second zone, 98°C in the third zone, a die temperature of 102°C, and a rotation speed of 50rpm; the POE raw material in S21 is placed in a twin-screw extruder, and melt blended at a temperature of 90°C in the first zone, 100°C in the second zone, 105°C in the third zone, a die temperature of 110°C, and a rotation speed of 50rpm; the material is cast through a co-extrusion cast film die head, and cooled through a casting roller; S23, film formation, i.e. After thickness measurement, edge pressing, shaping, edge trimming, and rolling, the light-converting film with a thickness of 500 μm is obtained; Among them, the EPE packaging light-converting film involved has a total thickness of 500μm.

[0059] In order to further understand the present invention, the photovoltaic organic-inorganic hybrid light conversion agent and light conversion adhesive film provided by the present invention are described in detail below in conjunction with specific embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0060] Example 1 A method for preparing an organic-inorganic hybrid light conversion agent comprises the following steps: S11, add benzotriazole to hydrobromic acid, stir, slowly add liquid bromine to the reaction system, heat and reflux for 20 hours; add saturated sodium bisulfite aqueous solution to quench, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and vacuum dry at 40°C for 8 hours to obtain intermediate I; The usage ratio of benzotriazole, hydrobromic acid, liquid bromine, saturated sodium bisulfite aqueous solution, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.75 mol: 0.14 mol: 400 mL: 300 mL: 5 g.

[0061] Its H NMR spectrum is shown in Figure 1 As shown, the H NMR spectrum data are as follows: 1 H NMR (400 MHz, CDCl3, δ ppm): 7.2-7.8 (3H, benzene ring); 10.22 (1H, -NH-).

[0062] S12, take the intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, add them to N,N-dimethylformamide, stir and heat at 50°C for 46 hours, cool to room temperature after the reaction is completed, wash with saturated ammonium chloride solution three times, extract with ethyl acetate, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 5, V / V), and dry in vacuo at 40°C for 8 hours to obtain the intermediate product II.

[0063] The usage ratio of intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, N,N-dimethylformamide, saturated ammonium chloride solution, ethyl acetate, and anhydrous sodium sulfate is 0.1 mol: 0.25 mol: 0.14 mol: 200 mL: 300 mL: 400 mL: 5 g.

[0064] Its H NMR spectrum is shown in Figure 2 As shown, the H NMR spectrum data are as follows: 1 H NMR (400MHz, CDCl3, δ ppm): 7.2-7.8(3H, benzene ring); 3.32(2H, -N-CH2-); 1.29(4H, -CH2-); 2.31(2H, -CH2-COO-); 1.20(9H, -CH3).

[0065] S13, take the intermediate product II, 4-(aniline)phenylboronic acid, potassium carbonate, and tetrakis(triphenylphosphine)palladium, mix them and add them to the reactor, and perform N2 replacement protection; after adding the mixed solvent, stir and heat under reflux for 20 hours; add deionized water and shake, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and dry in vacuo at 40°C for 8 hours to obtain the intermediate product III.

[0066] The usage ratio of intermediate II, 4-(aniline)phenylboronic acid, potassium carbonate, tetrakis(triphenylphosphine)palladium, mixed solvent, deionized water, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.14 mol: 0.5 mol: 0.008 mol: 150 mL: 200 mL: 300 mL: 5 g; The mixed solvent is toluene, n-butanol, and deionized water in a volume ratio of 3:5:1.

[0067] Its H NMR spectrum is shown in Figure 3 As shown, the H NMR spectrum data are as follows: 1 H NMR (400MHz, CDCl3, δ ppm): 7.2-7.8 (12H, benzene ring); 5.63 (1H, -NH-); 3.32 (2H, -N-CH2-); 1.29 (4H, -CH2-); 2.31 (2H, -CH2-COO-); 1.20 (9H, -CH3).

[0068] S14, the reaction system is replaced with N2 gas and protected with nitrogen, the intermediate product III is added to tetrahydrofuran A, magnetically stirred, n-butyl lithium is added, ice bath is placed, stirred for 15 minutes, and then added dropwise to tetrahydrofuran B containing 2,4,6-trichloro-1,3,5-triazine using a peristaltic pump. After the addition is completed, the mixture is heated under reflux for 6 hours; cooled to room temperature, deionized water is injected, stirred for 15 minutes, insoluble matter is obtained, the insoluble matter is filtered out, recrystallized with dichloromethane and n-hexane, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0069] The usage ratio of the intermediate product III, tetrahydrofuran A, n-butyl lithium, 2,4,6-trichloro-1,3,5-triazine, tetrahydrofuran B, and deionized water is 0.22 mol: 200 mL: 0.22 mol: 0.1 mol: 300 mL: 800 mL.

[0070] Its H NMR spectrum is shown in Figure 4 As shown, the H NMR spectrum data are as follows: 1 H NMR (400 MHz, CDCl3, δ ppm): 7.2-7.8 (24H, benzene ring); 3.32 (4H, -N-CH2-); 1.29 (8H, -CH2-); 2.31 (4H, -CH2-COO-); 1.20 (18H, -CH3).

[0071] S15, take the intermediate product IV and 4-aminophthalic acid, add them to anhydrous tetrahydrofuran, heat and reflux for 16 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, add saturated saline solution, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0072] The usage ratio of the intermediate product IV, 4-aminophthalic acid, anhydrous tetrahydrofuran, saturated saline solution and deionized water is 0.1 mol: 0.12 mol: 200 mL: 300 mL: 500 mL.

[0073] Its H NMR spectrum is shown in Figure 5 As shown, the H NMR spectrum data are as follows: 1 H NMR (400MHz, CDCl3, δ ppm): 7.2-8.0 (27H, benzene ring); 12.0-12.1 (2H, -COOH); 11.23 (1H, -NH-); 3.32 (4H, -N-CH2-); 1.29 (8H, -CH2-); 2.31 (4H, -CH2-COO-); 1.20 (18H, -CH3).

[0074] S16, adding the intermediate product V and tetrapod-shaped zinc oxide whiskers to anhydrous acetone, stirring magnetically at 85° C. for 2.5 h, introducing the mixture into a watch glass, and vacuum drying at 100° C. for 48 h to obtain an organic-inorganic hybrid light conversion agent.

[0075] The usage ratio of the intermediate product V, the tetrapod-shaped zinc oxide whisker, and anhydrous acetone is 1.0 g: 10 g: 200 mL.

[0076] Its H NMR spectrum is shown in Figure 6 As shown, the H NMR spectrum data are as follows: 1 H NMR (400MHz, δ ppm): 7.2-8.0 (27H, benzene ring); 11.23 (1H, -NH-); 3.32 (4H, -N-CH2-); 1.29 (8H, -CH2-); 2.31 (4H, -CH2-COO-); 1.20 (18H, -CH3).

[0077] An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.4 parts of coupling agent.

[0078] Example 2 A method for preparing an organic-inorganic hybrid light conversion agent comprises the following steps: S11, add benzotriazole to hydrobromic acid, stir, slowly drop liquid bromine into the reaction system, heat and reflux for 18 hours; add saturated sodium bisulfite aqueous solution to quench, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and vacuum dry at 40°C for 8 hours to obtain intermediate I; The usage ratio of benzotriazole, hydrobromic acid, liquid bromine, saturated sodium bisulfite aqueous solution, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.75 mol: 0.15 mol: 400 mL: 300 mL: 5 g.

[0079] S12, take the intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, add them to N,N-dimethylformamide, stir and heat at 60°C for 40 hours, cool to room temperature after the reaction is completed, wash with saturated ammonium chloride solution three times, extract with ethyl acetate, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 5, V / V), and dry in vacuo at 40°C for 8 hours to obtain the intermediate product II.

[0080] The usage ratio of intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, N,N-dimethylformamide, saturated ammonium chloride solution, ethyl acetate, and anhydrous sodium sulfate is 0.1 mol: 0.25 mol: 0.12 mol: 200 mL: 300 mL: 400 mL: 5 g.

[0081] S13, take the intermediate product II, 4-(aniline)phenylboronic acid, potassium carbonate, and tetrakis(triphenylphosphine)palladium, mix them and add them to the reactor, and perform N2 replacement protection; after adding the mixed solvent, stir and heat to reflux for 12 hours; add deionized water to shake, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate it by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and dry it in vacuo at 40°C for 8 hours to obtain the intermediate product III.

[0082] The usage ratio of intermediate II, 4-(aniline)phenylboronic acid, potassium carbonate, tetrakis(triphenylphosphine)palladium, mixed solvent, deionized water, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.16 mol: 0.5 mol: 0.01 mol: 150 mL: 200 mL: 300 mL: 5 g; The mixed solvent is toluene, n-butanol, and deionized water in a volume ratio of 3:5:1.

[0083] S14, the reaction system is replaced with N2 gas and protected with nitrogen, the intermediate product III is added to tetrahydrofuran A, magnetically stirred, n-butyl lithium is added, ice bath is placed, stirred for 15 minutes, and then added dropwise to tetrahydrofuran B containing 2,4,6-trichloro-1,3,5-triazine using a peristaltic pump. After the addition is completed, the mixture is heated under reflux for 8 hours; cooled to room temperature, deionized water is injected, stirred for 15 minutes, insoluble matter is obtained, the insoluble matter is filtered out, recrystallized with dichloromethane and n-hexane, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0084] The dosage ratio of the intermediate product III, tetrahydrofuran A, n-butyl lithium, 2,4,6-trichloro-1,3,5-triazine, tetrahydrofuran B, and deionized water is 0.20 mol: 200 mL: 0.20 mol: 0.1 mol: 300 mL: 800 mL.

[0085] S15, take the intermediate product IV and 4-aminophthalic acid, add them to anhydrous tetrahydrofuran, heat and reflux for 10 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, add saturated saline solution, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0086] The usage ratio of the intermediate product IV, 4-aminophthalic acid, anhydrous tetrahydrofuran, saturated saline solution and deionized water is 0.1 mol: 0.12 mol: 200 mL: 300 mL: 500 mL.

[0087] S16, adding the intermediate product V and tetrapod-shaped zinc oxide whiskers to anhydrous acetone, stirring magnetically at 90° C. for 2 h, introducing the mixture into a watch glass, and vacuum drying at 100° C. for 48 h to obtain the intermediate product V, i.e., an organic-inorganic hybrid light conversion agent.

[0088] The usage ratio of the intermediate product V, the tetrapod-shaped zinc oxide whisker, and anhydrous acetone is 1.0 g: 10 g: 200 mL.

[0089] An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 0.5 part of cross-linking agent; 3.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.3 parts of coupling agent.

[0090] Example 3 A method for preparing an organic-inorganic hybrid light conversion agent comprises the following steps: S11, add benzotriazole to hydrobromic acid, stir, slowly add liquid bromine to the reaction system, heat and reflux for 24 hours; add saturated sodium bisulfite aqueous solution to quench, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and vacuum dry at 40°C for 8 hours to obtain intermediate I; The usage ratio of benzotriazole, hydrobromic acid, liquid bromine, saturated sodium bisulfite aqueous solution, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.75 mol: 0.12 mol: 400 mL: 300 mL: 5 g.

[0091] S12, take the intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, add them to N,N-dimethylformamide, stir and heat at 40°C for 48 hours, cool to room temperature after the reaction is completed, wash with saturated ammonium chloride solution three times, extract with ethyl acetate, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 5, V / V), and dry in vacuo at 40°C for 8 hours to obtain the intermediate product II.

[0092] The usage ratio of intermediate product I, potassium carbonate, tert-butyl 5-bromovalerate, N,N-dimethylformamide, saturated ammonium chloride solution, ethyl acetate, and anhydrous sodium sulfate is 0.1 mol: 0.25 mol: 0.15 mol: 200 mL: 300 mL: 400 mL: 5 g.

[0093] S13, take the intermediate product II, 4-(aniline)phenylboronic acid, potassium carbonate, tetrakis(triphenylphosphine)palladium, mix them and add them to the reactor, and perform N2 replacement protection; after adding the mixed solvent, stir and heat under reflux for 24 hours; add deionized water to shake, extract with dichloromethane, separate the liquids, take the organic phase, add anhydrous sodium sulfate to dry, filter, take the solution, separate by column chromatography (eluent: petroleum ether / dichloromethane = 1 / 10, V / V), and dry in vacuo at 40°C for 8 hours to obtain the intermediate product III.

[0094] The usage ratio of intermediate II, 4-(aniline)phenylboronic acid, potassium carbonate, tetrakis(triphenylphosphine)palladium, mixed solvent, deionized water, dichloromethane, and anhydrous sodium sulfate is 0.1 mol: 0.12 mol: 0.5 mol: 0.005 mol: 150 mL: 200 mL: 300 mL: 5 g; The mixed solvent is toluene, n-butanol, and deionized water in a volume ratio of 3:5:1.

[0095] S14, the reaction system is replaced with N2 gas and protected with nitrogen, the intermediate product III is added to tetrahydrofuran A, magnetically stirred, n-butyl lithium is added, ice bath is placed, stirred for 15 minutes, and then added dropwise to tetrahydrofuran B containing 2,4,6-trichloro-1,3,5-triazine using a peristaltic pump. After the addition is completed, the mixture is heated under reflux for 5 hours; cooled to room temperature, deionized water is injected, stirred for 15 minutes, insoluble matter is obtained, the insoluble matter is filtered out, recrystallized with dichloromethane and n-hexane, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0096] The usage ratio of the intermediate product III, tetrahydrofuran A, n-butyl lithium, 2,4,6-trichloro-1,3,5-triazine, tetrahydrofuran B, and deionized water is 0.22 mol: 200 mL: 0.25 mol: 0.1 mol: 300 mL: 800 mL.

[0097] S15, take the intermediate product IV and 4-aminophthalic acid, add them to anhydrous tetrahydrofuran, heat and reflux for 20 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, add saturated saline solution, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0098] The usage ratio of the intermediate product IV, 4-aminophthalic acid, anhydrous tetrahydrofuran, saturated saline solution and deionized water is 0.1 mol: 0.1 mol: 200 mL: 300 mL: 500 mL.

[0099] S16, adding the intermediate product V and tetrapod-shaped zinc oxide whiskers to anhydrous acetone, stirring magnetically at 80° C. for 3 h, introducing the mixture into a watch glass, and vacuum drying at 100° C. for 48 h to obtain an organic-inorganic hybrid light conversion agent.

[0100] The usage ratio of the intermediate product V, the tetrapod-shaped zinc oxide whisker, and anhydrous acetone is 1.0 g: 10 g: 200 mL.

[0101] An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.5 parts of cross-linking agent; 1.0 part of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.5 parts of coupling agent.

[0102] Example 4 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S15, 4-aminophthalic acid is replaced by p-aminobenzoic acid.

[0103] Example 5 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S15, 4-aminophthalic acid is replaced by 1-aminobenzene-3,4,5-tricarboxylic acid.

[0104] Example 6 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent. In S16, the usage ratio of the intermediate product V, the tetrapod-shaped zinc oxide whisker, and the anhydrous acetone is 0.5 g:10 g:200 mL.

[0105] Example 7 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent. In S16, the dosage ratio of the intermediate product V, the tetrapod-shaped zinc oxide whisker, and the anhydrous acetone is 2.0 g:10 g:200 mL.

[0106] Example 8 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S16, the tetrapod-shaped zinc oxide whiskers are replaced with titanium oxide whiskers.

[0107] Example 9 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S16, the four-needle zinc oxide whiskers are replaced with copper oxide whiskers.

[0108] Example 10 The rest is the same as in Example 1, except that: An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.1 part; Light stabilizer 0.3 parts; 0.4 parts of coupling agent.

[0109] Embodiment 11 The rest is the same as in Example 1, except that: An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; 0.25 parts of antioxidant; Light stabilizer 0.1 part; 0.4 parts of coupling agent.

[0110] Example 12 The rest is the same as in Example 1, except that: An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 2.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.4 parts of coupling agent.

[0111] Example 13 The rest is the same as in Example 1, except that: An EVA light-transmitting adhesive film comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 10.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.4 parts of coupling agent.

[0112] Embodiment 14 The rest is the same as in Example 1, except that: A POE encapsulation light-converting adhesive film, comprising the following raw materials in parts by weight: POE resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.05 parts; Light stabilizer 0.05 parts; 0.8 parts of coupling agent.

[0113] Embodiment 15 The rest is the same as in Example 1, except that: An EPE encapsulation light-converting adhesive film comprises an EVA layer (100 μm thick) and a POE layer (300 μm thick). The EVA layer comprises the following raw materials in parts by weight: EVA resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; 0.2 parts of antioxidant; Light stabilizer 0.2 parts; 0.4 parts of coupling agent.

[0114] A POE encapsulation light-converting adhesive film, comprising the following raw materials in parts by weight: POE resin 100 parts; 1.0 part of cross-linking agent; 2.0 parts of auxiliary cross-linking agent; 6.0 parts of organic-inorganic hybrid light conversion agent; Antioxidant 0.05 parts; Light stabilizer 0.05 parts; 0.8 parts of coupling agent.

[0115] The following comparative examples are compared with Example 1: Comparative Example 1 The rest is the same as in Example 1, except that: An EVA light-converting adhesive film formula does not contain an organic-inorganic hybrid light-converting agent.

[0116] Comparative Example 2 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, S14, N2 is passed through the reaction system to replace gas and protected by nitrogen, the intermediate product III is added to toluene A, magnetic stirring is performed, palladium acetate and tert-butyl phosphine are added, and after stirring for 15 minutes, the mixture is added dropwise to toluene B containing 1,3,5-tribromobenzene by a peristaltic pump, and the mixture is heated to reflux for reaction. After the addition is completed, the reaction is continued for 3 hours; the mixture is cooled to room temperature, distilled under reduced pressure, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0117] The usage ratio of intermediate product III, toluene A, palladium acetate, tert-butyl phosphine, 1,3,5-tribromobenzene and toluene B is 0.22 mol: 200 mL: 1.1 mmol: 0.25 mol: 0.1 mol: 300 mL.

[0118] S15, take the intermediate product IV and 4-aminophthalic acid, add them to toluene, heat and reflux for 3 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, add saturated saline solution, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0119] The dosage ratio of the intermediate product IV, 4-aminophthalic acid, toluene, saturated saline solution and deionized water is 0.1 mol: 0.12 mol: 200 mL: 300 mL: 500 mL.

[0120] Comparative Example 3 The rest is the same as in Comparative Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent comprises the following steps: S14, the reaction system is replaced with N2 gas and protected with nitrogen, the intermediate product III is added to N,N-dimethylformamide A, and then added dropwise to N,N-dimethylformamide B containing 2,4,6-tribromomethyl-1,3,5-triazine and potassium carbonate using a peristaltic pump, and heated to 100°C for reflux reaction. After the addition is completed, the reaction is continued for 8 hours; cooled to room temperature, distilled under reduced pressure, and vacuum dried at 40°C for 8 hours to obtain the intermediate product IV.

[0121] The usage ratio of the intermediate product III, N,N-dimethylformamide A, 2,4,6-tribromomethyl-1,3,5-triazine, potassium carbonate and N,N-dimethylformamide B is 0.22 mol: 200 mL: 0.1 mol: 0.25 mol: 300 mL.

[0122] S15, take the intermediate product IV, 4-aminophthalic acid and potassium carbonate, add them to N,N-dimethylformamide, heat to 100°C and reflux for 6 hours, and use Ehrlich reagent to confirm the reaction endpoint; after the reaction is completed, distill and concentrate under reduced pressure, add saturated salt water solution to the concentrate, let it stand to produce insoluble matter, filter out the insoluble matter, rinse with deionized water, and vacuum dry at 40°C for 8 hours to obtain the intermediate product V.

[0123] The dosage ratio of intermediate product IV, 4-aminophthalic acid, potassium carbonate, N,N-dimethylformamide, saturated saline solution and deionized water is 0.1 mol: 0.12 mol: 0.12 mol: 200 mL: 300 mL: 500 mL.

[0124] Comparative Example 4 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S12, Replace tert-butyl 5-bromovalerate with butyl bromide.

[0125] Comparative Example 5 The rest is the same as in Example 1, except that: In an EVA light-converting adhesive film formula, an organic-inorganic hybrid light-converting agent is replaced by an intermediate product V.

[0126] Comparative Example 6 The rest is the same as in Example 1, except that: A method for preparing an organic-inorganic hybrid light conversion agent, wherein in S16, the tetrapod-shaped zinc oxide whiskers are replaced with spherical zinc oxide (with an average particle size of 50 nm); Spherical zinc oxide, product number Brofos-ZnO-50, was purchased from Brofos Nanotechnology (Ningbo) Co., Ltd.

[0127] Comparative Example 7 The rest is the same as in Example 1, except that: In an EVA light-converting film formula, an organic-inorganic hybrid light-converting agent is replaced by an intermediate product V and a tetrapod-shaped zinc oxide whisker in a dosage ratio of 1.0 g:10.g and then added.

[0128] The physical properties of the EVA light-converting adhesive films prepared in the examples of the present invention and the comparative examples were measured respectively, and the results are shown in Table 1.

[0129]

[0130] First, it can be concluded from Examples 1-15 in Table 1 that the photovoltaic organic-inorganic hybrid light conversion agent and light conversion adhesive film of the present invention have obvious advantages in improving the photoelectric conversion efficiency and other performances, and also have better aging resistance (stability).

[0131] Second, it can be observed from Example 1 and Comparative Example 1 that the light-converting adhesive film of the present invention uses a homemade organic-inorganic hybrid light-converting agent with excellent light-conversion efficiency. It can be observed from Example 1 and Comparative Examples 2-4 that the EVA adhesive film of the present invention uses a homemade organic-inorganic hybrid light-converting agent, and the triazine structure has a higher half-peak width and light-conversion efficiency than the benzene ring bonding; the direct bonding of the rigid group can further improve the light-conversion efficiency; in addition, the long-chain ester structure can improve the compatibility and further improve the comprehensive performance; it can be observed from Example 1 and Comparative Examples 5-6 that the enrichment of the inorganic whisker structure in the organic-inorganic hybrid light-converting agent has a significant effect on improving the light-conversion efficiency; and it has low migration performance; it can be observed from Example 1 and Comparative Example 7 that compared with simple physical blending, the organic-inorganic hybrid light-converting agent structure has obvious advantages in light-conversion efficiency, low migration, and photoelectric gain after surface modification of inorganic photosensitive metal oxides with organic light-converting structures.

[0132] Third, it can be observed from the examples that the light-transfer adhesive film of the present invention has a long-lasting high light-transfer efficiency, and thus should have excellent optical properties and stability.

[0133] In summary, the photovoltaic organic-inorganic hybrid light conversion agent and light conversion adhesive film of the present invention use a self-made light conversion agent and have excellent light conversion performance, low mobility, high stability and power gain function.

[0134] The test method is as follows: (1) Absorption half-peak width: Test the fluorescence excitation spectrum of the light conversion film.

[0135] (2) Light conversion efficiency: Horiba spectrometer FL-3, absolute quantum efficiency test was performed using an integrating sphere at room temperature.

[0136] (3) Resistance to humidity and heat aging: The film is subjected to humidity and heat aging test. Conditions: Test conditions: +85°C, relative humidity 85%.

[0137] The test was carried out before and after, and the retention rate was calculated according to the following formula: Retention rate = average value after the test / average value before the test × 100%.

[0138] (4) UV aging resistance: The obtained film was subjected to UV irradiation aging test according to the requirements of the International Electrotechnical Commission standard IEC61345. Test conditions: the surface temperature of the test piece is 60±5℃, the UV wavelength range is 280-400nm, and the irradiation intensity is 15kW·h / m 2 , the UV irradiation test time is 2000hr.

[0139] The test was carried out before and after, and the retention rate was calculated according to the following formula: Retention rate = average value after the test / average value before the test × 100%.

[0140] (5) Mobility test method: A rapid aging migration test is performed at the module end. The front of the photovoltaic module is a light-converting film doped with a light-converting agent, and the back of the module is a blank film without a light-converting agent (only the light-converting agent is a variable). After the module undergoes a UV300 aging test in the aging box, the film on the front of the module is removed and heated and soaked in an organic solvent (methanol) (stirring at 60°C, heating and soaking for 24 hours). The solution after soaking is analyzed by HPLC to obtain the content (A) of one embodiment. The film on the front of the module that has not been aged is removed, and the same heating and soaking treatment is performed. The solution after soaking is analyzed by HPLC to obtain the content (B) of another embodiment. The mobility is: A / B*100%.

[0141] (6) Photoelectric gain: Measured using an EL tester. Stack the photovoltaic glass, film, cell, film and photovoltaic backplane neatly from top to bottom, laminate at 140°C for 15 minutes, take out and cool, first test the bare chip power and record it as P 0.1 ; The power of the component obtained by laminating the film without adding adsorbent is tested and recorded as P1; the power of the new bare chip is tested and recorded as P 0.2 , the film of the present invention is used for lamination, and its power is tested and recorded as P2, then the power gain P m =(P2 / P 0.2 ) / (P1 / P 0.1 ).

[0142] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing an organic-inorganic hybrid light conversion agent, characterized in that: The following steps are involved: S11, subjecting benzotriazole to a substitution reaction with liquid bromine to obtain an intermediate product I; S12, subjecting the intermediate product I to a substitution reaction with a bromoester to obtain an intermediate product II; S13, coupling the intermediate product II with 4-(aniline)phenylboronic acid to obtain an intermediate product III; S14, subjecting the intermediate product III to a substitution reaction with 2,4,6-trichloro-1,3,5-triazine to obtain an intermediate product IV; S15, subjecting the intermediate product IV to a substitution reaction with an aminobenzoic acid derivative to obtain an intermediate product V; S16, surface modification of the intermediate product V and photosensitive metal oxide whiskers to obtain an organic-inorganic hybrid light conversion agent.

2. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The molar ratio of the benzotriazole to the liquid bromine is 1:(1.2-1.5).

3. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The molar ratio of the intermediate product I to the bromoester is 1:(1.2-1.5).

4. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The molar ratio of the intermediate product II to the 4-(aniline)phenylboronic acid is 1:(1.2-1.6).

5. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The molar ratio of the intermediate product III to the 2,4,6-trichloro-1,3,5-triazine is (2.0-2.2):

1.

6. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The molar ratio of the intermediate product IV to the aminobenzoic acid derivative is 1:(1.0-1.2); the aminobenzoic acid derivative has 1 amino functional group and 1-3 carboxyl functional groups.

7. The method for preparing the organic-inorganic hybrid light conversion agent according to claim 1, characterized in that: The mass ratio of the intermediate product V to the photosensitive metal oxide whisker is (0.5-2.0):10; the photosensitive metal oxide whisker is selected from at least one of zinc oxide, titanium oxide and copper oxide.

8. An organic-inorganic hybrid light conversion agent, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. A light-converting adhesive film, characterized in that: It comprises the organic-inorganic hybrid light conversion agent as described in claim 8.

10. The light conversion adhesive film according to claim 9, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polyolefin resin; Cross-linking agent 0.5-1.5 parts; 1.0-3.0 parts of auxiliary cross-linking agent; 2.0-10.0 parts of the organic-inorganic hybrid light conversion agent; Antioxidant 0.05-0.25 parts; Light stabilizer 0.05-0.3 parts; Coupling agent 0.3-0.8 parts.

11. The light-converting adhesive film according to claim 10, characterized in that: The polyolefin resin is selected from at least one of EVA resin and POE resin.

Citation Information

Patent Citations

  • Water-soluble compounds as light stabilizers

    CN1043728A

  • Light conversion adhesive film composition, light conversion adhesive film and photovoltaic module

    CN117431022A

  • EVA light conversion packaging adhesive film and preparation method thereof

    CN118638490A

  • Triazine organic light conversion agent, light conversion adhesive film composition, light conversion adhesive film and photovoltaic module

    CN118955476A

  • Insoluble s-triazine derivatives and their use as UV filters

    CN1240446A